Endometrial Thickness in Women Undergoing IUI With Ovarian Stimulation. How Thick Is Too Thin? A Systematic Review and Meta-analysis. Issue 8 (August 2017) - Weiss, N. S.; van Vliet, M. N.; Limpens, J.; Hompes, P. G. A.; Lambalk, C. B.; Mochtar, M. H.; van der Veen, F.; Mol, B. W. J.; van Wely, M.
Abstract : (Abstracted from Hum Reprod 2017;32:1009–1018) A simple, noninvasive first-line treatment for women diagnosed as having unexplained or mild male subfertility is intrauterine insemination with ovarian stimulation (IUI-OS). The drugs most frequently used for OS are antiestrogens, such as clomiphene citrate (CC), aromatase inhibitors, or gonodotrophins.